2019
DOI: 10.1039/c9tb01715a
|View full text |Cite
|
Sign up to set email alerts
|

Surface modificationviaplasmid-mediated pLAMA3-CM gene transfection promotes the attachment of gingival epithelial cells to titanium sheetsin vitroand improves biological sealing at the transmucosal sites of titanium implantsin vivo

Abstract: Modification of the transmucosal site of an implant by plasmid-mediated pLAMA3-CM gene transfection is a potential method for future clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 62 publications
0
21
1
Order By: Relevance
“…Representative images and the number of adherent cells indicated that Ad-LAMA3 treatment accelerates cellular attachment, consistent with the findings of a recent study. 28 However, we did not report any significant difference in day 1 in all of the groups regarding the proportion of wound healing. This is because HD depolymerization had not been fully activated.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Representative images and the number of adherent cells indicated that Ad-LAMA3 treatment accelerates cellular attachment, consistent with the findings of a recent study. 28 However, we did not report any significant difference in day 1 in all of the groups regarding the proportion of wound healing. This is because HD depolymerization had not been fully activated.…”
Section: Discussioncontrasting
confidence: 57%
“…8 , 26 , 27 More research evidence posits that the modification of LAMA3 to the implant surface through a gene-delivery vector promotes the biological sealing of the peri-implant epithelium. 21 , 28 Presently, we utilized the adenovirus vector to overexpress the LAMA3 gene due to its large size. Future studies should be conducted to identify the most pivotal functional fragment of the LAMA3 gene involved in the formation of HDs.…”
Section: Discussionmentioning
confidence: 99%
“…Atsuta et al reported that laminin332 induces cell migration during PIE formation after Ti implant placement in rats (Atsuta et al, 2005a,b). Wang et al (2019) indicated that the biological sealing around the transmucosal sites of implant could be promoted by the release of plasmid pLAMA3-CM (the C-terminal globular domain of LAMA3) from a titanium surface. These studies also showed that the leading edge of mucosal wound of sulcular epithelium and the underlying connective tissue express laminin332 during wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan has many applications in this field, as it can be used to coat surfaces in order to increase their biocompatibility and bioactivity [ 130 ]. Chitosan can also be conjugated with other substances, including AgNPs [ 131 , 132 ], hyaluronic acid [ 131 , 133 , 134 ], poly(dopamine) and hydroxyapatite [ 135 ], collagen [ 136 ], silica [ 137 ], and poly(acrylic acid) [ 138 ]. These substances, alongside chitosan, can prevent the surface adhesion of bacteria [ 131 , 132 , 133 , 134 , 138 ], increase the proliferation of cells [ 137 , 138 ], and improve osseointegration [ 134 ], soft tissue integration [ 135 ], and peri-implant tissue attachment [ 136 ].…”
Section: Peri-implantitis and Implant Failuresmentioning
confidence: 99%